Mind Travel of the Black Swan - Saif, L. Nishitha; Varsha K (International Journal of Psychosocial Rehabilitation, 2020)
Psychoanalytic theory and film studies have been agents of mutual influence from the time of birth of both disciplines. Psychoanalysis acts as a tool for an in- depth study of movies dealing with human subjects and minds. Movies portraying conflicts and dilemmas within individuals’ minds often prove worthy of psychoanalytical studies in turn providing insight into the functioning of the arte facts of human minds and giving new meanings to the pieces of art. This paper entitled “Mind Travel of the Black Swan”, aims to provide a psychoanalytic and psychodynamic approach to the movie Black Swan as a literary text on the basis of relevant findings about human mind put forward by major theorists, Sigmund Freud, Carl Gustav Jung, and Jacques Lacan. Cinema takes hold of the viewer’s analytical mind into a bizarre yet real world of subjective experience with deep running psychological conflicts. The collaborative and integrative study of psychoanalysis and film contribute to the growth of knowledge in both the areas of study. The study reflects how the modern digital society adopts and integrates the scattered information in digital media such as cinema to a whole different level of perception with the aid of theory and criticism. The paper opens a portal into the various psychoanalytic readings on the primary text with the aid of the strong theoretical framework of knowledge in film studies and psychoanalysis, aiming to enable further theoretical studies on the medium of cinema and the complex working of human minds.